2019
DOI: 10.1038/s41598-019-47278-2
|View full text |Cite
|
Sign up to set email alerts
|

Strong links promote the emergence of cooperative elites

Abstract: The maintenance of cooperative behavior is fundamental for the prosperity of human societies. Empirical studies show that high cooperation is frequently associated with the presence of strong social ties, but they are silent on whether a causal mechanism exists, how it operates, and what features of the social environment are conducive to its emergence. Here we show experimentally that strong ties increase cooperation and welfare by enabling the emergence of a close-knit and strongly bound cooperative elite. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…First, many of these studies do not allow for free neighborhood choice as we do but enforce dynamic interaction structures exogenously 4 , 31 , 32 . Second, most of these studies implement, implicitly or explicitly, an infinitely repeated game by either not telling subjects the number of total rounds or implementing a random ending 4 , 31 , 32 , 34 , 35 , 37 , which does not allow to investigate whether dynamic interaction structures also affect behavior when subjects know the end of the game. In fact, the social dilemma study closest to our research that implements a known horizon, finds that in most cases cooperation breaks down completely already well before the game ends 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, many of these studies do not allow for free neighborhood choice as we do but enforce dynamic interaction structures exogenously 4 , 31 , 32 . Second, most of these studies implement, implicitly or explicitly, an infinitely repeated game by either not telling subjects the number of total rounds or implementing a random ending 4 , 31 , 32 , 34 , 35 , 37 , which does not allow to investigate whether dynamic interaction structures also affect behavior when subjects know the end of the game. In fact, the social dilemma study closest to our research that implements a known horizon, finds that in most cases cooperation breaks down completely already well before the game ends 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, the reported effects of fluid interaction structures in social dilemma games are not uniformly and strongly positive. Most studies report mildly positive effects of dynamic interaction structures on cooperation that are, however, far off the fully efficient outcome 31 35 or—with one exception—not maintained in the long run 36 , 37 . Thus, direct evidence is needed on whether free choice of the interaction neighborhood helps individuals to coordinate fully and robustly on an efficient outcome in coordination problems.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental studies have shown homophily based on cooperativeness, i.e. cooperators tending to have more connections with other cooperators, increases when there is endogenous network formation (Wang et al, 2012), participants have complete information about the network structure (Gallo and Yan, 2015), and there is an opportunity to strengthen a connection (Gallo et al, 2019).…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
“…Previous studies (e.g. Gallo and Yan, 2015;Gallo et al, 2019) have shown that reputational information and a fastchanging social environment increase cooperation by enabling the formation of clusters of cooperators who associate with each other. We find that reputational uncertainty undermines this process in a fast-changing social environment because defectors are more likely to remain embedded in cooperators' neighborhoods thereby creating an obstacle to the formation of the cooperative clusters that would have driven up the cooperation level and average welfare of the whole group.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the reported effects of fluid interaction structures in social dilemma games are not uniformly and strongly positive. Most studies report mildly positive effects of dynamic interaction structures on cooperation that are, however, far off the fully efficient outcome 31,32,33,34,35 or-with one exception-not maintained in the long run 36,37 . Thus, direct evidence is needed on whether free choice of the interaction neighborhood helps individuals to coordinate fully and robustly on an efficient outcome in coordination problems.…”
Section: Introductionmentioning
confidence: 99%